From Sound to Satisfaction: How Perceived Music Quality and Place Shape Visitors' Intentions at Music Festivals - Jessyca Yulianty (Institut Seni Indonesia Padangpanjang, 2025)
Despite the growing prominence of music festivals as experiential tourism products, limited empirical research has integrated perceived music quality and place within a unified behavioral framework, particularly in emerging economies. This study investigates how perceived music quality and place influence visitors’ revisit intention, with satisfaction acting as a mediating variable. Drawing on the Stimulus Organism Response (SOR) framework, a quantitative research design was employed. Data were collected via an online questionnaire from 220 visitors who had attended large scale music festivals in Indonesia within the previous year. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test the proposed relationships. The findings indicate that both perceived music quality and place have significant positive effects on visitor satisfaction, with place exerting a substantially stronger influence. Moreover, satisfaction significantly mediates the effects of perceived music quality and place on revisit intention. The model demonstrates moderate to strong explanatory power, highlighting satisfaction as a key psychological mechanism linking festival attributes to behavioral intentions. This study extends the application of the SOR framework to music festival tourism in a developing country context and offers practical insights for festival organizers and destination managers seeking to enhance visitor satisfaction and foster repeat visitation through strategic improvements in musical performance and place-based experiences.